DIALEKTIKA EKONOMI ISLAM - Muh. Ruslan Abdullah (MUAMALAH, 2015)
Economics is an integral part in the dynamics of the struggle of Islamic thought. For a complete religion, Islam never opposed and contrary to the concept of economy, as long as the rules and norms outlined in the Qur'an and Sunnah. What distinguishes the economics and ethics of Islam with materialism. Islamic economics is a concept in an attempt to address the gap between scarcity and need no separateof islamic values